Explaining migration intention from selected psycho-social variables in South Wollo, Ethiopia - Assfaw, Abebe Kibret; Minaye, Abebaw (Frontiers in Sociology, 2022)
Migration has become one of the challenging global issues of the twenty-first century. Therefore, analyzing intention to migrate is essential to develop clear strategies to manage actual migration. This research aimed to investigate emigration intention predictors (namely place attachment, attitude, national pride, subjective social norm, and perceived behavioral control) and the interaction effect of social network between those predictors and migration intention. A sample of 701high school students participated in the research. Exploratory Factor Analysis and Confirmatory Factor Analysis were employed to explore the dimension and loading of items respectively. To test the moderation effect of social network on migration intention and the predicator variables, structural equation modeling was employed using Amos version 27. The findings indicated that Attitude, National pride, subjective social norm, and perceived behavioral control predict youths’ emigration intention. The result also revealed that social network strengthens the negative correlation between place attachment and intention to migrate only if the individuals have a high social network. The social network also moderates the relationship between attitude and emigration intention